Work Fatigue Levels Among Road Construction Workers Exposed To Sunlight - Nadiva, Adinda; Junaidi, Junaidi; Juanda, Juanda; Joko Supriyadi, Yohanes (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
The development of the construction and construction sector between contractors in Indonesia is growing rapidly and the death rate is increasing compared to the previous year. In general, the mortality rate is caused by the factor of length of work and the age of the worker. The reason is that age is no longer young when faced with a long job in a day, of course, it will also burden the physical, it's just that the difference caused by age will be decisive. This study aims to determine the relationship between the length of work and the age of workers with the level of work fatigue in road construction workers exposed to sunlight in North Hulu Sungai Regency. This study is an analytical test, with a cross sectional design. The population in this study amounted to 30 road construction workers and the research sample was taken from all populations. Data analysis using the Chisquare test. The results of the Chi-square statistical test showed that there was a relationship between working length and work fatigue p = 0.023 < 0.05 and there was a relationship between working age and work fatigue p = 0.029 < 0.05. It is recommended to optimize their rest time and be able to stretch their muscles between jobs. For companies, there is a limit on working hours of a maximum of 8 hours/day and urges workers to exercise before work.